Application of Science and Technology to Improve Productivity, Quality, and Marketing of Mocaf Bolen in Semarang City - Bahatmaka, Aldias; Ardiansari, Anindya; Fibriana, Fidia; Hidayat, Indra Nurul; Sari, Linda; Mayangsari , Effelie Dewi; Prasdika, Tegar Oki; Sandi Pratama , Fajar Rizqi (Edumedia Solution, 2025)
Micro, Small, and Medium Enterprises (MSMEs) make a significant contribution to economic growth, job creation, community empowerment, and the reduction of economic inequality. By 2023, MSMEs' contribution to Indonesia's GDP is projected to reach 61%, equivalent to IDR 9,580 trillion. The MSME sector absorbs 97% of the national workforce, representing approximately 117 million workers. The number of MSMEs also continues to grow each year, reaching 66 million in 2023, an increase from 65 million in 2022 (KADIN). MSME mentoring is a concrete step in supporting national aspirations, including increasing quality employment, encouraging entrepreneurship, developing creative industries, and supporting infrastructure development. In alignment with the SDGs, this PKM activity helps increase village community income and reduce income disparity. Additionally, MSMEs can apply appropriate technology (TTG) developed through university innovations. In this PKM program, the university’s IKU achievements for students and lecturers relate to IKU 2 and IKU 5, aligning with RIRN in the food sector concerning MSME empowerment for local food processing through TTG. The mentoring provides tangible benefits, with Appropriate Technology such as the Automatic Grinding Machine and Automatic Proofer Machine, resulting in a production increase to 500 Mocaf bolen per day from the original 350, reflecting a 42.86% rise. Furthermore, product diversification training was conducted by processing Mocaf flour into higher-value products such as Bolen Mocaf cookies and Mocaf Banana Bread. Digital marketing and business website mentoring were also implemented to strengthen promotional media, enabling products to access broader and potentially global markets